Masters of death eaudiobook A novel. - Blake, Olivie (Macmillan Audio, 2023)
"Steve West gives a lively performance of this fantasy/romance, voicing each mortal, immortal, and undead character with the requisite humor, sarcasm, and sinister whispers."- AudioFile F rom Olivie Blake, the New York Times bestselling author of The Atlas Six comes Masters of Death, a story about vampires, ghosts, and death itself! Viola Marek is a struggling real estate agent, and a vampire. But her biggest problem currently is that the house she needs to sell is haunted. The ghost haunting the house has been murdered, and until he can solve the mystery of how he died, he refuses to move on. Fox D'Mora is a medium, and though is also most-definitely a shameless fraud, he isn't entirely without his uses—seeing as he's actually the godson of Death. When Viola seeks out Fox to help her with her ghost-infested mansion, he becomes inextricably involved in a quest that neither he nor Vi expects (or wants). But with the help of an unruly poltergeist, a demonic personal trainer, a sharp-voiced angel, a love-stricken reaper, and a few high-functioning creatures, Vi and Fox soon discover the difference between a mysterious lost love and an annoying dead body isn't nearly as distinct as they thought. Also by Olivie Blake Alone With You in the Ether One For My Enemy The Atlas Six The Atlas Paradox A Macmillan Audio production from Tor Books.